1995
DOI: 10.1111/j.1525-1446.1995.tb00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing Nurses for a Changing Environmental Health Role

Abstract: This paper traces the evolution of a broader environmental health role for nursing by focusing on the health effects of exposure to environmental pollutants and of global environmental change. This evolving role is reviewed through the examination of selected community health nursing texts published during the last several decades. Key role strategies based on this expanded and evolving environmental role are proposed. Finally, a survey is described that is intended to heighten awareness of personal and profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
6
0
8
Order By: Relevance
“…An example of how ecological stability might impact health is by impacting disease vectors; a loss of biodiversity is postulated to contribute to an increased risk for exposure to Lyme disease (Ostfeld & Keesing, 2000). After reviewing EH content in nursing textbooks, Tiedje and Wood (1995) concluded that although nurses have begun to address the health risks posed by environmental toxins and carcinogens, they have yet to address global ecological hazards. A view of EH that includes ecological influences is also promoted by the National Environmental Health Association (Gordon, 1995) and the World Health Organization (1986).…”
Section: Environmental Healthmentioning
confidence: 99%
“…An example of how ecological stability might impact health is by impacting disease vectors; a loss of biodiversity is postulated to contribute to an increased risk for exposure to Lyme disease (Ostfeld & Keesing, 2000). After reviewing EH content in nursing textbooks, Tiedje and Wood (1995) concluded that although nurses have begun to address the health risks posed by environmental toxins and carcinogens, they have yet to address global ecological hazards. A view of EH that includes ecological influences is also promoted by the National Environmental Health Association (Gordon, 1995) and the World Health Organization (1986).…”
Section: Environmental Healthmentioning
confidence: 99%
“…, Nnoli ). Exposure was referenced by degree of severity as in ‘potential or excessive toxic exposure’ (Tiedje & Wood , Sattler & Lipscomb ) or used only if circumstances related to hazardous levels of toxic pollutants (Sattler et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of consequences, a third of the researchers' articles reviewed for this article described adverse consequences of exposure (i.e., symptoms or disease) rather than exposure per se (Rogers et al 2009, Nnoli 2011. Exposure was referenced by degree of severity as in 'potential or excessive toxic exposure' (Tiedje & Wood 1995, Sattler & Lipscomb 2003 or used only if circumstances related to hazardous levels of toxic pollutants (Sattler et al 2008). Exposure was described in terms of adverse health outcomes and posing a threat to human health (American Nurses Association 2007), causing a disease, having an impact on a condition, or adversely affecting health (Rogers 1994).…”
Section: In Environmental Health Nursingmentioning
confidence: 99%
See 2 more Smart Citations